2012
DOI: 10.2337/dc12-0269
|View full text |Cite
|
Sign up to set email alerts
|

Highly Purified Eicosapentaenoic Acid Increases Interleukin-10 Levels of Peripheral Blood Monocytes in Obese Patients With Dyslipidemia

Abstract: OBJECTIVEIt has recently been highlighted that proinflammatory (M1) macrophages predominate over anti-inflammatory (M2) macrophages in obesity, thereby contributing to obesity-induced adipose inflammation and insulin resistance. A recent clinical trial revealed that highly purified eicosapentaenoic acid (EPA) reduces the incidence of major coronary events. In this study, we examined the effect of EPA on M1/M2-like phenotypes of peripheral blood monocytes in obese dyslipidemic patients.RESEARCH DESIGN AND METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…In addition, a sub-analysis of the JELIS and other studies suggested that a high serum EPA/AA ratio is significantly associated with a low incidence of cardiac death or myocardial infarction, and a low coronary plaque score 14,15) . We also showed that the serum EPA/AA ratio in obese patients is associated with monocyte expression of IL-10, an antiinflammatory M2 marker 16) . DHA and EPA are n-3 PUFAs, and may contribute to the prevention of atherosclerosis and inflammatory diseases 11,17) .…”
Section: Study Protocolmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, a sub-analysis of the JELIS and other studies suggested that a high serum EPA/AA ratio is significantly associated with a low incidence of cardiac death or myocardial infarction, and a low coronary plaque score 14,15) . We also showed that the serum EPA/AA ratio in obese patients is associated with monocyte expression of IL-10, an antiinflammatory M2 marker 16) . DHA and EPA are n-3 PUFAs, and may contribute to the prevention of atherosclerosis and inflammatory diseases 11,17) .…”
Section: Study Protocolmentioning
confidence: 84%
“…terol Education Program-Adult Treatment Panel Ⅲ (NCEP-ATP Ⅲ) 29) , as described previously 16) . Of the 94 obese patients with dyslipidemia, six patients were excluded for the following reasons: five patients stopped consulting our clinic and one patient withdrew consent for their participation in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, diet-induced obesity decreased the expression of these genes in adipose tissue macrophages but increased the expression of genes encoding TNF-α and inducible nitric oxide synthase (iNOS) that are characteristic of M1 or "classically activated" macrophages 33) . In obese, dyslipidemic patients, n-3 PUFAs administration increased IL-10 expression in peripheral blood monocytes through a peroxisome proliferator-activated receptor (PPAR)-γ-dependent pathway, which indicates a shift from the M1 pro-inflammatory state to the M2-polarized state 32) . Furthermore, n-3-PUFAs inhibit Toll-like receptor 4 signaling on macrophages, which eventually suppresses adipose tissue inflammation and levels of inflammatory cytokines, including TNF-α, as well as the production of antiatherosclerotic hormones, especially adiponectin 7,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, n-3 PUFAs induce a shift from the M1 pro-inflammatory macrophage state to the M2-polarized macrophage state 32) . Adipose tissue macrophages of lean mice were found to express many genes that are characteristic of M2 or "alternatively activated" macrophages, such as arginase 1 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation